2021
DOI: 10.1021/acsagscitech.1c00177
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Preparation of Peanut-Bran-Derived Carbon Dots and Their Promoting Effect on Italian Lettuce

Abstract: In this research, we developed a simple, low-cost, and environmentally friendly method to prepare biomass carbon dots (CDs). We have obtained CDs with high yield, good water solubility, low toxicity, and excellent fluorescence performance by carbonizing peanut bran at high temperature. These CDs can be further used in agricultural production. We found that the peanut bran CDs had a dose−effect relationship on Italian lettuce growth. The fresh weight of the Italian lettuce cultivated under the appropriate conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…4E). 189 The abovementioned growth enhancement effects of CDs on various plants support their large-scale application in agriculture for enhancing crop growth and increasing agricultural yield.…”
Section: Environmental Science: Nano Tutorial Reviewmentioning
confidence: 93%
“…4E). 189 The abovementioned growth enhancement effects of CDs on various plants support their large-scale application in agriculture for enhancing crop growth and increasing agricultural yield.…”
Section: Environmental Science: Nano Tutorial Reviewmentioning
confidence: 93%
“…125 Lei et al used a simple carbonization method to successfully prepare peanut bran CDs, which showed great impact as a nanofertilizer in agriculture. 126 They found that the peanut bran CD solution effectively promotes the growth of Italian lettuce by increasing its nutrient absorption and significantly improving the utilization of chemical fertilizers. Similarly, photoluminescent carbon dots synthesized by thermal pyrolysis of the microalgae Spirulina were also reported as a fertilizer for stimulating agricultural plant growth.…”
Section: Biological and Environmental Impactsmentioning
confidence: 99%
“…125 Lei et al used a simple carbonization method to successfully prepare peanut bran CDs, which showed great impact as a nanofertilizer in agriculture. 126 They found that the peanut bran CD solution effectively promotes the growth of Italian lettuce by increasing its nutrient absorption and significantly improving the utilization of chemical fertilizers.…”
Section: Environmental Impactsmentioning
confidence: 99%
“…There are a number of precursors that can be used to obtain CDs. Some of them are based on plants and seeds, such as bamboo [13], peanut [14], watermelon [15], sago waste [16], walnut [17], osmanthus fragrans [18], strawberry [19], and banana [10]. Organic compounds like urea, ascorbic acid, and glucose are also reported as a precursor for CDs [10].…”
Section: Introductionmentioning
confidence: 99%